[BMIM] PF6 ionic liquid mediated green synthesis of ceramic SrO/CeO2 nanostructure using Pedalium murex leaf extract and their antioxidant and antibacterial activities. Issue 9 (15th June 2019) - Pandiyan, Nithya; Murugesan, Balaji; Sonamuthu, Jegatheeswaran; Samayanan, Selvam; Mahalingam, Sundrarajan
Abstract: Greener approaches of mixed oxide ceramic nanomaterial synthesis are the focus of recent developments. In this study, we report a facile and eco-friendly method with ionic liquid assisted green synthesis of ceramic SrO/CeO2 mixed oxide nanoparticles using ethanolic extraction of Pedalium murex (PM) leaf extract. An amount of 1-butyl-3-methyl imidazolium hexafluorophosphate [BMIM] PF6 ionic liquid is the mediator for the nucleation and morphology controlled growth process and plays the role of a surfactant and capping agent. Green synthesized ceramic SrO/CeO2 NPs displayed a nanorod-like structure and their crystallinity was examined by XRD studies. GC-MS spectroscopy was used to determine phytochemicals such as N-hexadecanoic acid (29%) and 6-octadecenoic acid (13%) present in the plant extract, which may act as a reducing agent for the synthesis of SrO/CeO2 NPs. The antibacterial investigation of SrO/CeO2 NPs exhibited excellent antibacterial activity compared with pristine SrO and CeO2 NPs. This antibacterial activity, when tested against strains of S. aureus and E-coli, showed that the SrO/CeO2 mixed oxide NPs were more liable for S. aureus (G + ) than E. coli (G − ) bacteria. Moreover, SrO/CeO2 mixed oxide NPs exhibited high antioxidant activity and reduced the DPPH free radical by up to 89%, because it produced a higher level of reactive oxygen species.